Bridging educational theories and practices: An interdisciplinary exploration of AI-driven pedagogical innovations in multicultural classrooms - Dwi Mariyono; Akmal Nur Alif Hd; Annis Nur AK (Ricerche di Pedagogia e Didattica)
This study explores the role of Artificial Intelligence (AI) in multicultural education through thematic analysis, content analysis, and cross-referencing analysis approaches. Drawing on current literature, the study identified key themes such as personalization of learning, cultural sensitivity in AI systems, ethical concerns and data bias, and professional development for educators. Content analysis assessed the frequency of occurrence of these themes across educational materials, while cross-referencing analysis integrated findings from both previous methods to provide a more comprehensive understanding. The results show that AI has great potential to support multicultural education, but there are significant gaps in its implementation, especially related to cultural sensitivity and professional development for educators. These findings highlight the need for more focused strategies to ensure AI is used ethically and inclusively in culturally diverse educational contexts.